PROFIL GERAKAN DAKWAH DI KOTA PALU - Akmal Salim Ruhana (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
The internal harmony of Muslims is influenced by the religious proselytizing implementation of the organizations or individuals. The difference in the character and role of their proselytizing practices especially in the same working field, often cause light conflicts. This paper describes the dynamics of the actors of religious proselytizing missions in the city of Palu, namely: Al-Khairaat, NU, DDI, and Muhammadiyah, and the number of potential conflicts and integration in activities influenced upon the people. The qualitative research which is descriptiveanalytical has discovered that these issues are no longer facing khilafiyah confronted towards them, but the political dynamics among religious organizations indeed tend to potentially interfere with the relationship between them. In that regard, the maturity and growth of the people as well as the level of education in empowering togetherness internal forums Muslims will be able to strengthen their relationship.